Factors that Influence Taxpayer Compliance with information Knowledge Technology as a Moderating Variable - Riska Natariasari; Eka Hariyani (Indonesian Journal of Economics, Social, and Humanities, 2023)
This research examines how accounting processes, attitudes toward tax incentives, and knowledge of tax laws affect taxpayer compliance. Analyzing information technology knowledge can help to minimize the impact of accounting procedures and tax law knowledge on taxpayer compliance. The participants in this research are the registered KPP Pratama Pekanbaru Senapelan culinary MSME taxpayers. 397 respondents were selected as samples using the purposive sampling technique and primary data. SEM-Partial Least Square is the analytical method used is SEM-Partial Least Square (PLS). According to the study's findings, accounting procedures help ensure that taxpayers comply with the law. Tax incentives help taxpayer compliance in a beneficial way. There is no connection between tax law comprehension and taxpayer compliance. The link between accounting procedures and taxpayer compliance can be moderated by having a solid understanding of information technology. The relationship between tax incentive views and compliance by taxpayers can be moderated by knowledge of information technology. The relationship between comprehending tax laws and taxpayer compliance cannot be moderated by information technology knowledge.